Testing of the mechanical properties of reggranulate PVC with the addition of plasticizer from waste PET - Vuksanović, Marija; Milošević, Milena; Knežević, Nataša; Egelja, Adela; Janković-Mandić, Ljiljana; Mladenović, Ivana; Marinković, Aleksandar (Tehnika (Beograd), 2023)
The subject of this research is the production process of polyvinyl chloride (PVC) regranulate using a plasticizer synthesized from recycled poly(ethylene terephthalate) (PET). In this way, a plasticizer was synthesized that does not pose a risk to human health and the environment in accordance with the principles of chemical leasing and green chemistry. The obtained plasticizer was characterized using elemental analysis, FTIR, and NMR spectroscopy and determination of hydroxyl and acid number. The mechanical properties of materials obtained on the basis of recycled PVC and plasticizers from PET were tested according to standard methods.